Unleashing Society's Innovative Capacity An Integrated Policy Framework - Braunerhjelm, Pontus; Henrekson, Magnus (International Studies in Entrepreneurship,, 2024)
This is an open access book. Europe faces significant challenges in the coming decades: geopolitical, demographic, technological, increased competition, climate-related, and health issues due to an aging population, to mention a few. Given these challenges, technological progress and new ways of handling complex issues will be key to continued prosperity and growth. To accomplish a growth process driven by innovation and entrepreneurship, the institutional environment must take into account a multitude of different policy areas that interact to either strengthen or weaken an economy's innovative potential. Innovation is not only about R&D and higher education but is also intimately related to entrepreneurship. Similarly, entrepreneurship is not only about low start-up costs and favorable tax rates. Hence, a consistent and coordinated policy environment conducive to innovation and entrepreneurship is required to translate innovation into high-growth firms and macro-level growth. This book presents the basic cornerstones required to provide a policy regime that can nurture such dynamics. The authors draw extensively on empirical analysis of the development of the Swedish economy, which has been transformed from a so-called "sclerosis" state in the 1980s until the early 1990s to an economy characterized by successful entrepreneurship and innovation. This transformation resulted from a reform agenda that has been gradually rolled out, beginning in the mid-1980s. The authors argue that the Swedish experience provides useful lessons for other nations as well.